اردو مثنوی میں تصویر کاری اور محاکات نگاری کی روایت - Rehman, Dr. Tasneem (Zoraiz, 2022)
Masnavi has been an important part of Urdu poetry. Masnavi demands the characteristics of an artist from the composer. Urdu masnavi is full of vibrant images of society and lively pictures of nature. In this article, the author analyses the multiple styles and topics of pictures combined by poets of Urdu masnavi.